Therapeutic Low-Intensity Ultrasound for Peripheral Nerve Regeneration – A Schwann Cell Perspective - Acheta, Jenica; Stephens, Shannon B. Z.; Belin, Sophie; Poitelon, Yannick (Frontiers in Cellular Neuroscience, 2022)
Peripheral nerve injuries are common conditions that can arise from trauma (e.g., compression, severance) and can lead to neuropathic pain as well as motor and sensory deficits. Although much knowledge exists on the mechanisms of injury and nerve regeneration, treatments that ensure functional recovery following peripheral nerve injury are limited. Schwann cells, the supporting glial cells in peripheral nerves, orchestrate the response to nerve injury, by converting to a “repair” phenotype. However, nerve regeneration is often suboptimal in humans as the repair Schwann cells do not sustain their repair phenotype long enough to support the prolonged regeneration times required for successful nerve regrowth. Thus, numerous strategies are currently focused on promoting and extending the Schwann cells repair phenotype. Low-intensity ultrasound (LIU) is a nondestructive therapeutic approach which has been shown to facilitate peripheral nerve regeneration following nerve injury in rodents. Still, clinical trials in humans are scarce and limited to small population sizes. The benefit of LIU on nerve regeneration could possibly be mediated through the repair Schwann cells. In this review, we discuss the known and possible molecular mechanisms activated in response to LIU in repair Schwann cells to draw support and attention to LIU as a compelling regenerative treatment for peripheral nerve injury.